2021
DOI: 10.1055/s-0041-1733955
|View full text |Cite
|
Sign up to set email alerts
|

Early Vital Sign Differences in Very Low Birth Weight Infants with Severe Intraventricular Hemorrhage

Abstract: Objective Severe intraventricular hemorrhage (sIVH, grades 3 and 4) is a serious complication for very low birth weight (VLBW) infants and is often clinically silent requiring screening cranial ultrasound (cUS) for detection. Abnormal vital sign (VS) patterns might serve as biomarkers to identify risk or occurrence of sIVH. Study Design This retrospective study was conducted in VLBW infants admitted to two level-IV neonatal intensive care units (NICUs) between January 2009 and December 2018. Inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In many patients, spontaneous intracerebral hemorrhage is caused by nontraumatic factors, and their mortality and disability rates are extremely high [ 1 3 ]. If an intracerebral hemorrhage breaks into the ventricle, it may quickly lead to a rapid increase in intracranial pressure, acute dilation of the ventricle, and compression of the ventricle system by a hematoma, resulting in acute obstructive hydrocephalus [ 4 , 5 ]. These patients will develop critical disease quickly, with rapid onset, rapid progression, high mortality, and poor prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many patients, spontaneous intracerebral hemorrhage is caused by nontraumatic factors, and their mortality and disability rates are extremely high [ 1 3 ]. If an intracerebral hemorrhage breaks into the ventricle, it may quickly lead to a rapid increase in intracranial pressure, acute dilation of the ventricle, and compression of the ventricle system by a hematoma, resulting in acute obstructive hydrocephalus [ 4 , 5 ]. These patients will develop critical disease quickly, with rapid onset, rapid progression, high mortality, and poor prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of absolute values, Vesoulis et al [ 43 ] studied 645 infants born <32 weeks of GA and proposed that the time spent with SpO 2 ≤ 70% was associated with severe grade III and IV IVH. Moreover, a lower level of SpO 2 was associated with IVH grades III and IV in very low birth weight infants [ 44 ]. However, in the current study, we did not find an association between features extracted from the SpO 2 signal, including and excluding PRDs or with time spent below SpO 2 ≤ 85%, with IVH outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Low SD of HR values displayed on standard NICU monitors is a simple measurement of HR variability, whereas the more traditional measure of HRV is SD of interheartbeat intervals which requires analysis of QRS complexes from the electrocardiogram waveform. We and others have reported low HRV to be associated with acute brain injury in both term and preterm neonates 9 11 16 18 19 27 and one aim of the current work was to discover simple metrics which do not require waveform analysis. In addition to low HR SD, negative skewness of HR was retained in the final CP model likely reflecting the fact that HR decelerations can be associated with pathology.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,16 In subsequent work, we reported that preterm infants with severe intraventricular hemorrhage (IVH) have lower HR variability for several weeks after birth compared with those with no or low-grade IVH, perhaps reflecting chronic neuroinflammation. 18,19 In those studies, HR variability analysis was performed by analyzing electrocardiogram QRS complexes and using various measurements such as standard deviation (SD) of interbeat intervals. Since R peak detection in electrocardiogram is not readily available, our recent research has utilized a simpler method of analyzing the SD of the HR displayed on NICU bedside monitors, as well as the SpO 2 from the pulse oximeter.…”
mentioning
confidence: 99%